Sustainable Investments and Divestments by Global Institutional Investors - Olga V. Khmyz (Финансовый журнал, 2024)
The article analyzes the investment activity of sustainable institutional investors after the global financial and economic crisis of 2008. The relevance of the study is conditioned, firstly, by the leading positions of institutional investors in the global financial market and in the system of international finance; secondly, by the special role of mutual funds and ETFs in the global market of sustainable finance; thirdly, by the noticeable dynamics of investments by these market participants in recent years, which increasingly turns into divestments. The purpose of the study is to identify current trends in sustainable investment by global institutional investors and formulate their further actions in the short term. To do this, it is necessary to solve the following tasks: to clarify, taking into account the latest statistical data, the impact of the COVID-19 pandemic and other force majeure factors on the size and dynamics of the flow of funds of sustainable institutional investors in the leading countries of the world, and to assess the impact on investment prospects of current political and financial factors. In the course of the study, a significant amount of scientific research was analyzed, which served as a basis for identifying the institutional investors’ approaches to sustainable finance. It is concluded that the prospects for global sustainable investing are favorable due to the continued stimulation of environmental change at the supranational level, both in developed and leading developing countries. The financial success of sustainable investment will also contribute to this.